Correlation of production constraints with the yield gap of apple cropping systems in Luochuan County, China - Dong ZHANG; Chong WANG; Xiao-lin LI; Xiu-shan YANG; Lu-bang ZHAO; Shao-jie XIA (Journal of Integrative Agriculture, 2019)
Apple occupies a dominant position in fruit production globally, and has become the main income source of local smallholder farmers in Luochuan County in the Loess Plateau area, one of the largest apple production areas in China. However, the annual productivity of apple orchards in this region remains low and has gradually declined over the years. The distinction and correlation of production constraints can contribute to the promotion of apple orchard productivity and the development of a sustainable orchard system. In the present study, survey data from 71 smallholder farmers were analyzed using a yield gap model to distinguish the production constraints and determine their correlation with the yield gap based on the structural equation model (SEM). The results indicated that the average apple yield in Luochuan County was 29.9 t ha−1 yr−1, while the attainable yield (Yatt; the highest yield obtained from the on-farm surveys) was 58.1 t ha−1 yr−1. The average explained and unexplainable yield gaps were 26.3 and 1.87 t ha−1 yr−1. According to the boundary line analysis, crop load, number of sprayings and base fertilizer N were the top three constraints on apple production in 9.8, 7.8 and 7.8% of the plots, respectively. Among the production constraints, crop load and fruit weight affected apple yield through direct pathways, whereas other constraints influenced apple yield through an indirect pathway based on the SEM, explaining 51% of the yield variance by all the main production constraints. These results can improve the current understanding of production constraints and contribute to the development of management strategies and policies for improving apple yield.